THE ACTIVITY OF ANTIOXIDANTS ENZYMES AND NPK CONTENTS AS AFFECTED BY WATER QAULITY, KINETIN, BIO AND ORGANIC FERTILIZATION IN LETTUCE (Lactuca sativa L.) - & Majid, Altaey (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2018)
A field experiment was conducted using split – split block design to study the effect of irrigation water quality ,organic composts ,kinetin and Bio- health application on N.P.K contents and anti-oxidant enzymes activity in lettuce, The experiment included three factors ,quality of irrigation water (W) at two levels (1.2, 6.1 dS m-1 ), kind of organic composts Plam fronds and Rice wastes(20) ton /hectare , kinetin application (50 mg.L-1) and bio-health fertilizers (5 kg/ hectare). The results indicated that elevation of water salinity levels led to elevation in activity of Peroxidase POX , Catalase CAT, Malondialdehyde MDA, Superoxide dismutase SOD enzymes and proline contents in leaves, while it decrease leaves contents of ( N.P.K), Organic composts , kinetin and bio-health applications alleviated from the negative effects of saline water by increasing the (NPK) contents in leaves ,reduced POX ,CAT, MDA,SOD and proline , That possible to mitigation the negative affect of salt stress in lettuce the application of plant growth regulators , bio fertilizers and decomposed organic matter.